RELIABILITY OF FLIGHT DATA PROVIDED BY PORTABLE GPS RECEIVERS DURING AIR ACCIDENT INVESTIGATION - V. M. Rukhlinskiy; S. V. Zayko; A. S. Dyachenko (Научный вестник МГТУ ГА)
This article considers the problem of assessment of data authenticity related to reliability of the flight data obtained in processing the information of portable GPS receivers’ during air accident investigations, which are characterized by the lack of standard flight data recording systems. Appropriate recommendations the improvement improving of the newly developed GPS receivers have been developed and implemented.